Educación e inclusión financiera en México y Colombia - Saucedo Loera, Laura Adriana; Oropeza Tagle, Miguel Ángel; Ruíz Guerra, Ricardo (RAN, 2024)
Diseño/Metodología: Para contrastar la educación financiera se analizaron las Estrategias Nacionales de Educación Financiera de ambas naciones utilizando la técnica de investigación cualitativa conocida como análisis de contenido. En cuanto a la inclusión financiera se utilizó The Global Index; considerando el uso de productos financieros y regresiones lineales como técnica econométrica de análisis. Resultados: En términos generales, los dos países muestran similitud en sus resultados.Implicaciones prácticas: Pero, resalta el hecho de que Colombia aborda la previsión para el retiro y protección para la vejez como argumento particular dentro de su plan de acción en su Estrategia Nacional de Educación Económica y Financiera, lo que muestra como consecuencia números superiores en la variable “preocupación sobre el futuro”, en contraste con México.Originalidad/Valor: Lo anterior contribuye a que estos países puedan afinar sus estrategias financieras. Purpose: The objective of this study is to conduct a comparative analysis of financial education and inclusion between Mexico and Colombia. Design/Methodology: To contrast financial literacy, we employ the qualitative research technique of content analysis to examine national strategies of financial education in both nations. For financial inclusion, we utilize the Global Index, considering the usage of financial products and employ linear regressions as an econometric analysis technique. Results: In general, both countries showed similarities in their results. Practical implications: Nevertheless, it is noteworthy that Colombia addressed the subject of “retirement welfare and old-age protection” as a central theme in their National Strategy for Economic and Financial Education. This emphasis resulted in a higher quantity in the variable “concern about the future” compared to Mexico. Originality/Value: This study results may prove valuable to improve financial strategies in both nations.